Method for molding fiber-reinforced composite material and epoxy resin composition used therein

The method of using a specific epoxy resin composition with epoxy resins, isocyanate curing agents, and catalysts in the formation of fiber-reinforced composite materials addresses the issues of low impact resistance and toughness, achieving improved heat resistance and mechanical balance for aerospace and automobile applications.

JP7647101B2Active Publication Date: 2025-03-18TORAY INDUSTRIES INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020564680
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-03
Filing Date
2020-11-16
Publication Date
2025-03-18
Estimated Expiration
2040-11-16

AI Technical Summary

Technical Problem

Existing fiber-reinforced composite materials suffer from low impact resistance and toughness due to the use of low molecular weight thermosetting resins, and previous solutions have either compromised toughness or led to brittle products.

Method used

A method for forming fiber-reinforced composite materials using an epoxy resin composition that includes epoxy resins with at least two oxirane groups, an epoxy resin curing agent with at least two isocyanate groups, and a catalyst, cured to achieve a specific absorbance ratio and relationship between elastic modulus and glass transition temperature.

Benefits of technology

The approach results in fiber-reinforced composite materials with enhanced toughness and heat resistance without compromising the balance of mechanical properties, making them suitable for aerospace and automobile applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647101000001
    Figure 0007647101000001
  • Figure 0007647101000002
    Figure 0007647101000002
  • Figure 0007647101000003
    Figure 0007647101000003
Patent Text Reader

Abstract

The present invention addresses the problem of providing: an epoxy resin composition for fiber-reinforced composite materials which retains a low viscosity during injection into reinforcing fibers to show excellent infiltrating properties and which comes to have both high toughness and high heat resistance; and a fiber-reinforced composite material obtained using the epoxy resin composition. The present invention is characterized by a method for forming a fiber-reinforced composite material which comprises reinforcing fibers [A] and a cured object obtained from an epoxy resin composition [B], wherein the epoxy resin composition [B] comprises the following constituent elements [a], [b], and [c] and is cured so that the absorbance ratio Da / (Da+Db) comes to be in the range of 0.4-1, thereby obtaining the fiber-reinforced composite material. [a]: An epoxy resin having at least two oxirane groups in the molecule [b]: An epoxy resin hardener having at least two isocyanate groups in the molecule [c]: A catalyst
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for molding a fiber-reinforced composite material suitable for aerospace and automotive applications, and an epoxy resin composition used therein. [Background technology]

[0002] Fiber-reinforced composite materials (FRP), which consist of reinforcing fibers and matrix resin, can be designed to take advantage of the advantages of both reinforcing fibers and matrix resin, and their uses are expanding to include aerospace, sports, and general industrial fields.

[0003] As the reinforcing fibers, glass fibers, aramid fibers, carbon fibers, boron fibers, etc. are used. As the matrix resin, both thermosetting resins and thermoplastic resins are used, but thermosetting resins are often used from the viewpoints of heat resistance and productivity. As the thermosetting resins, epoxy resins, unsaturated polyester resins, vinyl ester resins, phenolic resins, bismaleimide resins, cyanate resins, etc. are used. Among them, epoxy resins are preferably used from the viewpoints of adhesion between the resin and the reinforcing fibers, dimensional stability, and mechanical properties such as strength and rigidity of the resulting composite material.

[0004] Fiber-reinforced composite materials are manufactured by a method such as a prepreg method, a hand lay-up method, a filament winding method, a pultrusion method, an RTM (Resin Transfer Molding) method, a film bag molding method, a press molding method, etc. In particular, when productivity is required, the RTM method, the film bag molding method, and the press molding method, which are excellent in productivity, are preferably used.

[0005] As described above, the matrix resin used in the conventional molding method of fiber-reinforced composite materials is a low-molecular-weight thermosetting resin that is liquid or semi-solid at room temperature in order to ensure sufficient impregnation into the reinforcing fiber substrate. Fiber-reinforced composite materials using such resins have a major problem in that the impact resistance of the fiber-reinforced composite materials is relatively low because the toughness of the cured product of the thermosetting resin is generally low compared to that of thermoplastic resins.

[0006] In response to this, in recent years, the development of preforms in which a binder containing thermoplastic resin is placed between layers and matrix resins with improved toughness has progressed, and their application to the primary structure of carbon fiber reinforced composite materials (CFRP) has also been considered. In particular, matrix resins that combine low viscosity with high toughness and high heat resistance are one of the important technologies that determine the above molding technologies, and there are high expectations for improvements in the matrix resins themselves.

[0007] Among these, it is known that the application of a matrix resin containing a liquid isocyanate curing agent improves toughness and heat resistance while maintaining low viscosity (Patent Documents 1 and 2).

[0008] Patent Document 1 discloses a technology for preparing an epoxy resin composition having excellent heat resistance, which is intended for use as a sealant or coating material, by using a liquid isocyanate as a curing agent and 0.001 to 1 mass % of diazabicycloundecene as a catalyst and curing the composition in a medium temperature range of 70 to 100°C.

[0009] Patent Document 2 discloses a technique for obtaining an epoxy resin composition that cures in a short time at low temperature and has excellent heat resistance and toughness by adding a polyol to an epoxy resin composition that uses an excess amount of isocyanate as a curing agent.

[0010] Patent Document 3 shows that the heat resistance of the cured product can be improved by compounding a large excess of isocyanate that has been pre-reacted with a polyol in the range of 3 to 20 equivalents with epoxy and promoting an oxazolidone cyclization reaction using a Lewis acid-base catalyst. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] International Publication No. 2014 / 184082 [Patent Document 2] International Publication No. 2016 / 102358 [Patent Document 3] International Publication No. 2019 / 046382 Summary of the Invention [Problem to be solved by the invention]

[0012] The matrix resin described in Patent Document 1 favorably promotes self-polymerization of isocyanate by medium temperature curing, and mainly forms isocyanurate rings that have excellent heat resistance. However, since such rings have three bonding points, they tend to have a high crosslink density and do not have excellent toughness.

[0013] The matrix resin described in Patent Document 2 was prone to deterioration and thickening due to hydrolysis specific to urethane bonds, etc. In addition, since it contains an excessive amount of isocyanate, it is prone to producing isocyanurate rings, and when this material is used to make a fiber-reinforced composite material, very brittle parts are formed, which can lead to a decrease in the balance of mechanical properties.

[0014] The matrix resin described in Patent Document 3 contains a large excess of isocyanate, which results in the production of many isocyanurate rings, making the cured product brittle and preventing the production of a fiber-reinforced composite material having excellent toughness and heat resistance.

[0015] An object of the present invention is to overcome the drawbacks of the conventional techniques and to provide a resin composition excellent in toughness and heat resistance, and a fiber-reinforced composite material using the same. [Means for solving the problem]

[0016] In order to achieve the above-mentioned object, the present invention provides, as a first aspect thereof, a method for molding a fiber-reinforced composite material comprising at least a reinforcing fiber [A] and a cured product of an epoxy resin composition [B], wherein the epoxy resin composition [B] contains the following components [a], [b], and [c], and the epoxy resin composition [B] is cured so that an absorbance ratio Da / (Da+Db) is in the range of 0.4 to 1 to obtain the fiber-reinforced composite material. [a] Epoxy resin having at least two oxirane groups in the molecule [b] An epoxy resin curing agent having at least two isocyanate groups in the molecule [c]Catalyst (Here, the absorbance ratio is determined by calculating the absorbance ratio Da / (Da+Db) from the absorbance Da of the absorption due to the C=O double bond of the carboxyl group of the oxazolidone ring and the absorbance Db of the absorption due to the C=O double bond of the carboxyl group of the isocyanurate ring in FT-IR (ATR method).) As a second aspect of the method for molding a fiber-reinforced composite material, there is provided a method for molding a fiber-reinforced composite material comprising at least reinforcing fibers [A] and a cured product of an epoxy resin composition [B], wherein the epoxy resin composition [B] contains the following components [a], [b], and [c], and the epoxy resin composition [B] is cured so that the relationship between the rubber state elastic modulus (Gr) and the glass transition temperature (Tg) satisfies Formula 1 to obtain the fiber-reinforced composite material. [a] Epoxy resin having at least two oxirane groups in the molecule [b] An epoxy resin curing agent having at least two isocyanate groups in the molecule [c]Catalyst Tg≧10×Gr+120 (Formula 1) A first aspect of the epoxy resin composition for use in a fiber-reinforced composite material is an epoxy resin composition for use in a fiber-reinforced composite material, which comprises the following components [a], [b], and [c], and when cured while increasing the temperature from 30°C at a rate of 10°C / min, the absorbance ratio Da / (Da+Db) at a degree of cure X% is in the range of 85-95%, such that the degree of cure X is in the range of 0.4-1. [a] Epoxy resin having at least two oxirane groups in the molecule [b] An epoxy resin curing agent having at least two isocyanate groups in the molecule [c]Catalyst (Here, the degree of cure is determined by calculating the total calorific value QT of the epoxy resin composition obtained by DSC and the residual calorific value QR of the cured product of the epoxy resin composition, as follows: degree of cure (%) = (QT - QR) / QT x 100.) A second aspect of the epoxy resin composition for fiber-reinforced composite materials is an epoxy resin composition for fiber-reinforced composite materials, which comprises the following components [a], [b], and [c], and when cured while increasing the temperature from 30°C at a rate of 10°C / min, a specific degree of cure X exists in the range of 85 to 95%, where the relationship between the rubber state elastic modulus (Gr) and the glass transition temperature (Tg) at the degree of cure X satisfies Equation 1. [a] Epoxy resin having at least two oxirane groups in the molecule [b] An epoxy resin curing agent having at least two isocyanate groups in the molecule [c]Catalyst Tg≧10×Gr+120 (Formula 1) Further provided are cured products of these epoxy resin compositions and fiber-reinforced composite materials using the same. Effect of the Invention

[0017] According to the present invention, by using a thermosetting resin that cures under specific conditions and by using a molding method that cures under specific conditions, a fiber-reinforced composite material that has excellent toughness and heat resistance without compromising the balance of mechanical properties can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The method for molding a fiber-reinforced composite material and the epoxy resin composition for a fiber-reinforced composite material (hereinafter, sometimes simply referred to as "epoxy resin composition") of the present invention will be described in detail below.

[0019] In the method for molding a fiber-reinforced composite material of the present invention, an epoxy resin composition [B] is used in common to the first and second embodiments. Such an epoxy resin composition must contain an epoxy resin having at least two oxirane groups in the molecule as component [a], an epoxy resin curing agent having at least two isocyanate groups in the molecule as component [b], and a catalyst as component [c]. In the following description, when the first or second embodiment is not particularly specified and the method for molding a fiber-reinforced composite material is described, this means that the method for molding a fiber-reinforced composite material is common to the first and second embodiments. (The same applies to the epoxy resin composition for fiber-reinforced composite material).

[0020] The component [a] in the molding method for fiber-reinforced composite material of the present invention is an epoxy resin having at least two oxirane groups in the molecule. By having such a structure, the mechanical properties and moldability of the fiber-reinforced composite material can be obtained. Among them, the component [a] is preferably an epoxy resin having a number average molecular weight in the range of 200 to 800 and containing an aromatic group in the skeleton, because it has low viscosity, excellent impregnation into reinforcing fibers, and excellent mechanical properties such as heat resistance and elastic modulus when made into a fiber-reinforced composite material. The number average molecular weight is determined by, for example, GPC (Gel Permeation Chromatography) using a polystyrene standard sample, but when the epoxy equivalent is known, a value calculated from the product of the epoxy equivalent and the number of epoxy functional groups can also be used.

[0021] Examples of the epoxy resin having at least two oxirane groups in the molecule used in the method for molding a fiber-reinforced composite material of the present invention include bisphenol-type epoxy resins and amine-type epoxy resins.

[0022] Examples of bisphenol type epoxy resins used in the molding method for fiber reinforced composite materials of the present invention include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD ​​type epoxy resins, and halogen- or alkyl-substituted or hydrogenated products thereof. Among them, bisphenol F type epoxy resins are preferably used because of their excellent balance between high elastic modulus and high toughness. Specific examples of such bisphenol type epoxy resins include the following.

[0023] Commercially available bisphenol A type epoxy resins include jER (registered trademark) 825, jER (registered trademark) 827, and jER (registered trademark) 828 (all manufactured by Mitsubishi Chemical Corporation), EPICLON (registered trademark) 840, and EPICLON (registered trademark) 850 (all manufactured by DIC Corporation), Epotohto (registered trademark) YD-128, Epotohto (registered trademark) YD-8125, and Epotohto (registered trademark) YD-825GS (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), DER (registered trademark) 331, and DER (registered trademark) 332 (all manufactured by The Dow Chemical Company, Ltd.), and the like.

[0024] Commercially available bisphenol F type epoxy resins include, for example, jER (registered trademark) 806, jER (registered trademark) 807, jER (registered trademark) 4004P (all manufactured by Mitsubishi Chemical Corporation), EPICLON (registered trademark) 830 (manufactured by DIC Corporation), Epototo (registered trademark) YD-170, Epototo (registered trademark) YDF-8170C, Epototo (registered trademark) YDF-870GS (all manufactured by Nippon Steel Chemical & Material Co., Ltd.).

[0025] Commercially available bisphenol AD ​​type epoxy resins include, for example, EPOX-MK R710 and EPOX-MK R1710 (both manufactured by Printec Co., Ltd.).

[0026] Examples of the amine-type epoxy resins used in the method for molding a fiber-reinforced composite material of the present invention include tetraglycidyldiaminodiphenylmethane, tetraglycidyldiaminodiphenylsulfone, triglycidylaminophenol, triglycidylaminocresol, diglycidylaniline, diglycidyltoluidine, tetraglycidylxylylenediamine, and halogen- or alkyl-substituted or hydrogenated products thereof. Specific examples of such epoxy resins include the following.

[0027] Commercially available products of tetraglycidyldiaminodiphenylmethane include "Sumiepoxy (registered trademark)" ELM434 (manufactured by Sumitomo Chemical Co., Ltd.), YH434L (manufactured by Nippon Steel Chemical & Material Co., Ltd.), "jER (registered trademark)" 604 (manufactured by Mitsubishi Chemical Corporation), "Araldite (registered trademark)" MY720, and "Araldite (registered trademark)" MY721 (all manufactured by Huntsman Advanced Materials).

[0028] An example of a commercially available product of tetraglycidyldiaminodiphenyl sulfone is TG3DAS (manufactured by Mitsui Fine Chemicals, Inc.).

[0029] Commercially available triglycidyl aminophenol or triglycidyl aminocresol products include Sumiepoxy (registered trademark) ELM100 and Sumiepoxy (registered trademark) ELM120 (both manufactured by Sumitomo Chemical Co., Ltd.), Araldite (registered trademark) MY0500, Araldite (registered trademark) MY0510, and Araldite (registered trademark) MY0600 (all manufactured by Huntsman Advanced Materials), and jER (registered trademark) 630 (manufactured by Mitsubishi Chemical Corporation).

[0030] Commercially available diglycidyl aniline products include GAN (manufactured by Nippon Kayaku Co., Ltd.) and PxGAN (manufactured by Toray Fine Chemicals Co., Ltd.).

[0031] Commercially available diglycidyl toluidine products include GOT (manufactured by Nippon Kayaku Co., Ltd.).

[0032] Commercially available tetraglycidylxylylenediamine and its hydrogenated products include "TETRAD (registered trademark)"-X and "TETRAD (registered trademark)"-C (both manufactured by Mitsubishi Gas Chemical Co., Ltd.). Among these, tetraglycidyldiaminodiphenylmethane and triglycidyldiaminophenol are preferably used because they have both a high elastic modulus and high heat resistance.

[0033] The component [a] preferably contains one or more amine-type epoxy resins and / or one or more bisphenol-type epoxy resins. The combined use of an amine-type epoxy resin and a bisphenol-type epoxy resin is preferred from the viewpoint of improving the balance between the high elastic modulus, high heat resistance, and high toughness.

[0034] The component [b] in the molding method for a fiber-reinforced composite material of the present invention is an epoxy resin curing agent having at least two isocyanate groups in the molecule, and the isocyanate groups react mainly with the oxirane groups of the component [a] to form an oxazolidone ring, which has a rigid skeleton and can exhibit high heat resistance. Among them, the component [b] containing an aromatic group in the skeleton is preferably used because it imparts higher heat resistance.

[0035] Examples of the epoxy resin curing agent having at least two isocyanate groups in the molecule used in the molding method for the fiber-reinforced composite material of the present invention include aliphatic isocyanates such as methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, trimethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, propylene-1,2-diisocyanate, 2,3-dimethyltetramethylene diisocyanate, butylene-1,2-diisocyanate, butylene-1,3-diisocyanate, 1,4-diisocyanate hexane, cyclopentene-1,3-diisocyanate, isophorone diisocyanate, 1,2,3,4-tetraisocyanate butane, butane-1,2,3-triisocyanate, and α,α,α',α'-tetramethylxylylene diisocyanate. Examples of the isocyanate include aromatic isocyanates such as benzene-1,2,4-triisocyanate, p-phenylene diisocyanate, 1-methylphenylene-2,4-diisocyanate, naphthalene-1,4-diisocyanate, tolylene diisocyanate, diphenyl-4,4-diisocyanate, benzene-1,2,4-triisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate (MDI), diphenylpropane diisocyanate, tetramethylene xylene diisocyanate, and polymethylene polyphenyl polyisocyanate; alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, lysine diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate; and those having a structure in which these are linked via a methylene group or the like. These polyisocyanate compounds may be used alone or in combination of two or more.

[0036] Commercially available aliphatic isocyanates include HDI (manufactured by Tosoh Corporation), Duranate (registered trademark) D101, and Duranate (registered trademark) D201 (manufactured by Asahi Kasei Corporation).

[0037] Commercially available aromatic isocyanates include "Rupranate (registered trademark)" MS, "Rupranate (registered trademark)" MI, "Rupranate (registered trademark)" M20S, "Rupranate (registered trademark)" M11S, "Rupranate (registered trademark)" M5S, "Rupranate (registered trademark)" T-80, "Rupranate (registered trademark)" MM-103, "Rupranate (registered trademark)" MM-102, and "Rupranate (registered trademark)" MM-301 (all manufactured by BASF INOAC Co., Ltd.). Polyurethane Co., Ltd.), "Millionate (registered trademark)" MT, "Millionate (registered trademark)" MT-F, "Millionate (registered trademark)" MT-NBP, "Millionate (registered trademark)" NM, "Millionate (registered trademark)" MR-100, "Millionate (registered trademark)" MR-200, "Millionate (registered trademark)" MR-400, "Coronate (registered trademark)" T-80, "Coronate (registered trademark)" T-65, "Coronate (registered trademark)" T-100 (all manufactured by Tosoh Corporation), "Cosmonate (registered trademark)" PH, "Cosmonate (registered trademark)" M-50, "Cosmonate (registered trademark)" T-80 (all manufactured by Mitsui Chemicals, Inc.), etc.

[0038] Commercially available alicyclic isocyanates include "Takenate (registered trademark)" 600 (manufactured by Mitsui Chemicals, Inc.) and "Fortimo (registered trademark)" 1,4-H6XDI (manufactured by Mitsui Chemicals, Inc.).

[0039] A product obtained by pre-reacting an epoxy resin with an epoxy resin curing agent can also be blended into the epoxy resin composition. This method can be effective in adjusting viscosity and improving storage stability.

[0040] The component [c] in the molding method for a fiber-reinforced composite material of the present invention is a catalyst, which is a compound capable of promoting a curing reaction by oxazolidone cyclization between the oxirane group contained in the component [a] and the isocyanate group contained in the component [b]. By including such a catalyst, the curing reaction proceeds under appropriate conditions, and the oxazolidone cyclization reaction proceeds preferentially over side reactions such as isocyanurate ring formation, forming a molecular structure that is rigid and has a low crosslinking density, thereby making it possible to obtain a molded product that has excellent moist heat resistance and toughness.

[0041] The catalyst used in the molding method for fiber-reinforced composite material of the present invention is not particularly limited, but is preferably a basic catalyst, a salt of a Brønsted acid and a base, or an onium salt whose anion is a halide, more preferably an amine or a derivative thereof, an ammonium salt, an imidazole or a derivative thereof, or an imidazolium salt. These catalysts may be used alone or in combination of two or more kinds.

[0042] In addition to using the epoxy resin composition [B] described above, in the first embodiment of the method for molding a fiber-reinforced composite material of the present invention, it is essential to obtain a fiber-reinforced composite material by curing the epoxy resin composition [B] so that the absorbance ratio Da / (Da+Db) is in the range of 0.4 to 1.

[0043] By setting the absorbance ratio Da / (Da+Db) in the range of 0.4 to 1, preferably in the range of 0.5 to 1, and more preferably in the range of 0.7 to 1, it is possible to form a structure with a low crosslink density while maintaining heat resistance, and obtain a cured product with high toughness. If the absorbance ratio Da / (Da+Db) is lower than 0.4, the crosslink density becomes too high, and the strength and toughness of the obtained fiber reinforced composite material decrease. Note that the closer the absorbance ratio Da / (Da+Db) is to 1, the lower the crosslink density and the more excellent the heat resistance tends to be, and this is preferable.

[0044] The absorbance ratio here means a value calculated as the absorbance ratio Da / (Da+Db) using FT-IR with attenuated total reflection (hereinafter sometimes simply referred to as the "ATR method") from the absorbance Da of the absorption due to the C=O double bond of the carboxyl group of the oxazolidone ring of the cured product of the epoxy resin composition and the absorbance Db of the absorption due to the C=O double bond of the carboxyl group of the isocyanurate ring. For example, when FT-IR (ATR method) is used with a resolution of 4 cm -1 When the measurement was performed 32 times, the result was 1760 cm -1 The absorbance of the absorption near 1710cm -1 It can be calculated by taking the absorbance of the absorption near Db.

[0045] In a first embodiment of the method for molding a fiber-reinforced composite material of the present invention, it is preferable to cure the epoxy resin composition [B] so that at a specific degree of cure within a range of 15 to 25%, the absorbance ratio Da / (Da+Db) is in the range of 0.01 to 1. That is, in the first embodiment of the method for molding a fiber-reinforced composite material of the present invention, it is preferable to cure the epoxy resin composition [B] so that at a certain degree of cure within a range of 15 to 25% (for example, a degree of cure of 20%) the absorbance ratio Da / (Da+Db) is in the range of 0.01 to 1.

[0046] The absorbance ratio Da / (Da+Db) of the epoxy resin composition [B] at a certain degree of cure within the range of 15-25% is in the range of 0.01-1, preferably in the range of 0.05-1, more preferably in the range of 0.1-1, so that it is possible to suppress the reaction in which oxazolidone ring formation takes precedence over isocyanurate ring formation, that is, the reaction which tends to increase the crosslink density, and to avoid significant viscosity increase at the initial stage of curing. If the absorbance ratio Da / (Da+Db) of the epoxy resin composition [B] at a certain degree of cure within the range of 15-25% is lower than 0.01, a highly heat-resistant structure can be expected, but the resulting fiber-reinforced composite material will be brittle. In addition, it does not have sufficient viscosity, which leads to deterioration of surface quality.

[0047] The degree of cure described here is a value determined by calculating the degree of cure (%) from the total heat release QT of the epoxy resin composition [B] obtained by differential scanning calorimetry (DSC) and the residual heat release QR of the cured product of the epoxy resin composition [B], as follows: degree of cure (%) = (QT - QR) / QT x 100. For example, the degree of cure can be calculated by measuring the epoxy resin composition [B] by DSC at a temperature rise rate of 10°C / min in the temperature range from 30°C to 350°C, with QT being the total heat release, and measuring the cured product of the epoxy resin composition [B] with QR being the residual heat release.

[0048] In a second aspect of the method for molding a fiber-reinforced composite material of the present invention, it is essential that the same epoxy resin composition [B] as in the first aspect is used, and this epoxy resin composition [B] is cured so that the relationship between the rubber state elastic modulus (Gr) and the glass transition temperature (Tg) satisfies formula 1, to obtain a fiber-reinforced composite material.

[0049] As described above, the oxazolidone ring is preferentially generated during curing, and as a result, a molecular structure that is rigid and has a low crosslinking density is formed, and the relationship between Gr and Tg satisfies formula 1, preferably formula 1a, and more preferably formula 1b. As a result, a cured product and a fiber-reinforced composite material having high heat resistance and excellent toughness can be obtained. If the relationship between Gr and Tg does not satisfy formula 1, the balance between heat resistance and toughness of the obtained fiber-reinforced composite material will not be good. It is preferable that the relationship between Gr and Tg also satisfies formula 1'. Tg≧10×Gr+120 (Formula 1) Tg≧10×Gr+140 (Formula 1a) Tg≧10×Gr+160 (Formula 1b) Tg≦10×Gr+230 (Formula 1') In a second aspect of the method for molding a fiber-reinforced composite material of the present invention, it is preferable to obtain a fiber-reinforced composite material by curing the epoxy resin composition [B] so that the rubber-state elastic modulus (Gr) satisfies formula 2.

[0050] When Gr satisfies formula 2, more preferably formula 2a, and even more preferably formula 2b, a structure with a low crosslink density can be formed, and a cured product with high toughness can be obtained. When Gr does not satisfy formula 2, the toughness of the obtained fiber-reinforced composite material may be insufficient. 0.5≦Gr≦15 (Formula 2) 0.5≦Gr≦10 (Formula 2a) 0.5≦Gr≦5 (Formula 2b) The glass transition temperature herein is the midpoint temperature determined in accordance with JIS K7121:1987 by measuring the temperature of a cured epoxy resin product by heating it from 30°C to 350°C at a heating rate of 10°C / min using a differential scanning calorimeter.

[0051] Here, the rubber state elastic modulus is a value measured as follows. That is, an epoxy resin composition is heat-cured into a plate having a thickness of about 2 mm, which is processed into a test piece having a width of 12±1 mm and a length of 30 to 40 mm, and then dynamic viscoelasticity is measured with a dynamic viscoelasticity measuring device at a temperature rise rate of 5°C / min. The rubber state elastic modulus is the storage elastic modulus at a temperature 50°C higher than the glass transition temperature obtained by dynamic viscoelasticity measurement. The glass transition temperature obtained by dynamic viscoelasticity measurement is the temperature at the intersection of a tangent drawn to the glass region and a tangent drawn to the glass transition region in the temperature-storage elastic modulus curve.

[0052] In the method for molding a fiber-reinforced composite material of the present invention, the epoxy resin composition [B] is preferably cured so that its mass loss rate ΔWr measured by thermogravimetric analysis (TGA) satisfies a range of 10% or less to obtain a fiber-reinforced composite material.

[0053] Here, the mass reduction rate is a value calculated by calculating the mass reduction rate ΔWr(%)=(W1-W2) / W1×100 from the sample mass W1 at 70°C and the sample mass W2 at 320°C when thermogravimetric analysis is performed at a heating rate of 10°C / min from 50°C to 800°C in a non-oxidizing atmosphere at normal pressure. ΔWr can be calculated by a general thermogravimetric analysis, but the atmosphere used in this analysis is a non-oxidizing atmosphere at normal pressure. A non-oxidizing atmosphere refers to an atmosphere that does not substantially contain oxygen, that is, an inert gas atmosphere such as nitrogen, helium, or argon. If ΔWr exceeds 10, for example, the heat resistance and compressive strength under moist heat of the fiber-reinforced composite material may not be sufficiently ensured.

[0054] The epoxy resin composition [B] used in the molding method for fiber-reinforced composite material of the present invention has the characteristics of a small initial viscosity increase, a long injectable time, and curing in a short time. Therefore, it is most suitable for the RTM method in which the mold temperature is kept constant from injection to demolding, but it can also be applied to any molding method using a liquid thermosetting resin, such as an RTM method in which the temperature is raised after the resin is injected and then cured, or other molding methods such as hand layup, pultrusion, and filament winding, and is effective in shortening the molding time and improving the impregnation of reinforcing fibers in any molding method.

[0055] The method for molding the fiber-reinforced composite material of the present invention will be explained in more detail by taking the above-mentioned RTM method as an example. The fiber-reinforced composite material is produced by injecting the above-mentioned epoxy resin composition [B] into a substrate made of reinforcing fibers [A] placed in a mold heated to 100 to 200°C, impregnating the substrate with the epoxy resin composition [B], and curing the substrate in the mold.

[0056] In such a molding method, the epoxy resin composition [B] before injection is preferably heated to a constant temperature. The heating temperature is determined from the perspective of the impregnation into the base material made of the reinforcing fiber [A] and the relationship between the initial viscosity and the viscosity increase of the epoxy resin composition [B], and is preferably 30 to 80°C, more preferably 40 to 70°C.

[0057] The molding temperature of the fiber-reinforced composite material (heat curing temperature of the epoxy resin composition [B]) can be adjusted by heating the mold, and the temperature of the heated mold is preferably in the range of 100 to 200 ° C., more preferably in the range of 120 to 180 ° C. By setting the molding temperature of the fiber-reinforced composite material within the above range, it is possible to shorten the time required for curing while avoiding significant thickening in the early stage of curing of the epoxy resin composition [B], which is the matrix resin of the fiber-reinforced composite material, and at the same time, to reduce the thermal shrinkage after demolding the fiber-reinforced composite material, thereby obtaining a fiber-reinforced composite material with good surface quality. In addition, the absorbance ratio Da / (Da+Db) of the cured product of the epoxy resin composition [B] is high and △Wr is small, so that a fiber-reinforced composite material with an excellent balance between toughness and heat resistance can be obtained.

[0058] In addition, in the molding method of the fiber-reinforced composite material, when the epoxy resin composition [B] is injected into the substrate made of the reinforcing fiber [A] arranged in the mold, it is preferable to inject the resin from multiple locations provided in the mold. Specifically, it is preferable to use a mold having multiple injection ports and to select appropriate conditions according to the fiber-reinforced composite material to be obtained, such as injecting the epoxy resin composition [B] from the multiple injection ports simultaneously or sequentially with a time difference, in order to have a degree of freedom to accommodate molded products of various shapes and sizes. There is no limit to the number or shape of such injection ports, but the more the number of injection ports, the better in order to enable injection in a short time, and the position of the injection ports is preferably such that the flow length of the resin can be shortened according to the shape of the molded product.

[0059] The injection pressure when injecting the epoxy resin composition [B] is usually 0.1 to 1.0 MPa, and from the viewpoint of injection time and equipment economy, 0.1 to 0.6 MPa is preferred. Vacuum-Assisted Resin Transfer Molding (VaRTM) method can also be used in which the inside of the mold is evacuated and the epoxy resin composition [B] is injected. Even when pressure injection is performed, it is preferable to evacuate the inside of the mold before injecting the epoxy resin composition [B], since this can prevent the generation of voids.

[0060] In the molding method for a fiber-reinforced composite material of the present invention, the reinforcing fiber [A] is preferably glass fiber, aramid fiber, carbon fiber, boron fiber, etc. Among them, carbon fiber is preferably used because it is possible to obtain a fiber-reinforced composite material that is lightweight yet has excellent mechanical properties such as strength and elastic modulus.

[0061] As the carbon fiber, any kind of carbon fiber can be used depending on the application, but from the viewpoint of impact resistance, it is preferable that the carbon fiber has a tensile modulus of at most 400 GPa. From the viewpoint of strength, it is preferable that the carbon fiber has a tensile strength of 4.4 GPa or more and 6.5 GPa or less, since a composite material having high rigidity and mechanical strength can be obtained. In addition, the tensile elongation is also an important factor, and it is preferable that the carbon fiber has a high strength and high elongation of 1.7% or more and 2.3% or less. Therefore, a carbon fiber having the characteristics of a tensile modulus of at least 230 GPa, a tensile strength of at least 4.4 GPa, and a tensile elongation of at least 1.7% is particularly suitable.

[0062] The reinforcing fibers [A] may be either short fibers or continuous fibers, or a combination of both. In order to obtain a fiber-reinforced composite material with a high Vf, continuous fibers are preferred.

[0063] In the molding method for a fiber-reinforced composite material of the present invention, the reinforcing fiber [A] may be used in the form of a strand, but a substrate made of the reinforcing fiber [A] processed into a form such as a mat, woven fabric, knit, braid, unidirectional sheet, etc. is preferably used. Among them, a woven fabric is preferably used because it is easy to obtain a fiber-reinforced composite material with a high Vf and has excellent handling properties.

[0064] The ratio of the net volume of the reinforcing fiber [A] to the apparent volume of the fabric is the packing ratio of the fabric. The packing ratio of the fabric is expressed as the basis weight W (unit: g / m 2 ), thickness t (unit: mm), density of reinforcing fiber ρf (unit: g / cm 3) by the formula W / (1000t ρf). The basis weight and thickness of the fabric are determined in accordance with JIS R7602:1995. Since a fiber reinforced composite material with a high Vf is more easily obtained when the filling rate of the fabric is high, the filling rate of the fabric is preferably within the range of 0.10 to 0.85, preferably 0.40 to 0.85, and more preferably 0.50 to 0.85.

[0065] In order for the fiber-reinforced composite material obtained by the molding method for fiber-reinforced composite material of the present invention to have a high specific strength or specific elastic modulus, its fiber volume fraction Vf is preferably within the range of 40 to 85%, preferably 45 to 85%. The fiber volume fraction Vf of the fiber-reinforced composite material referred to here is a value defined and measured as follows in accordance with ASTM D3171 (1999), and refers to the state after injecting a thermosetting resin [B] into a substrate made of reinforcing fiber [A] and curing it. That is, the fiber volume fraction Vf of the fiber-reinforced composite material can be calculated using the following formula from the thickness h of the fiber-reinforced composite material, etc. Vf(%)=(Af×N) / (ρf×h) / 10 Af: 1 sheet of base material made of reinforcing fiber [A] x 1 m 2 Mass per unit (g / m 2 ) N: Number of layers of the base material made of reinforcing fiber [A] (sheets) ρf: Density of reinforcing fiber [A] (g / cm 3 ) h: Thickness of the fiber-reinforced composite material (test piece) (mm).

[0066] In addition, from the fiber-reinforced composite material, 1 substrate made of reinforcing fiber [A] × 1 m 2 In order to specify the mass Af per unit area, the number of layers N of the substrate made of the reinforcing fiber [A], and the density ρf of the reinforcing fiber [A], the substrate made of the reinforcing fiber [A] may be separated and taken out from the fiber-reinforced composite material by either the combustion method, the nitric acid decomposition method, or the sulfuric acid decomposition method based on JIS K7075:1991. The density of the reinforcing fiber [A] used in this case is the value measured based on JIS R7603:1999.

[0067] The thickness h of the fiber-reinforced composite material is preferably measured with a micrometer specified in JIS B7502:1994 or with a micrometer having an accuracy equal to or higher than that, as described in JIS K7072:1991. If the fiber-reinforced composite material has a complex shape and is difficult to measure, a sample (a sample having a certain shape and size for measurement) may be cut out from the fiber-reinforced composite material and measured.

[0068] One of the preferred forms of the fiber-reinforced composite material obtained by the method for molding a fiber-reinforced composite material of the present invention is a veneer. Other preferred forms include a sandwich structure in which a veneer-shaped fiber-reinforced composite material is arranged on both sides of a core material, a hollow structure surrounded by a veneer-shaped structure, and a so-called canape structure in which a veneer-shaped fiber-reinforced composite material is arranged on one side of a core material.

[0069] Examples of the core material for the sandwich structure and the canape structure include a honeycomb core made of aluminum or aramid, a foam core made of polyurethane, polystyrene, polyamide, polyimide, polyvinyl chloride, phenolic resin, acrylic resin, epoxy resin, etc., wood such as balsa, etc. Among them, a foam core is preferably used as the core material because it can provide a lightweight fiber-reinforced composite material.

[0070] The epoxy resin composition for fiber-reinforced composite materials of the present invention essentially comprises, as component [a], an epoxy resin having at least two oxirane groups in its molecule, as component [b], an epoxy resin curing agent having at least two isocyanate groups in its molecule, and as component [c], a catalyst.

[0071] The component [a] in the epoxy resin composition for a fiber-reinforced composite material of the present invention is an epoxy resin having at least two bonded oxirane groups in the molecule, and the same as that explained in the method for molding a fiber-reinforced composite material of the present invention is preferably used.

[0072] The component [b] in the epoxy resin composition for fiber-reinforced composite materials of the present invention is an epoxy resin curing agent consisting of a compound containing at least two bonded isocyanate groups in the molecule and having an active group capable of reacting with the oxirane group of the component [a], and the same as that explained in the method for molding a fiber-reinforced composite material of the present invention is preferably used.

[0073] In the epoxy resin composition for fiber-reinforced composite materials of the present invention, the ratio of the number of moles of isocyanate groups of the component [b] to the number of moles of oxirane groups of all epoxy resins contained in the epoxy resin composition is preferably 0.5 to 1.8, more preferably 0.8 to 1.5, even more preferably 0.8 to 1.1, and even more preferably 0.95 to 1.05. If the ratio of the number of moles of isocyanate groups to the number of moles of oxirane groups of all epoxy resins contained in the epoxy resin composition of the present invention is less than 0.5, self-polymerization by the oxirane groups of the component [a] tends to proceed, and there is a risk of insufficient heat resistance. On the other hand, if the ratio exceeds 1.8, there is a risk of high crosslink density and insufficient resin elongation. In addition, if there is an excess of highly reactive isocyanate groups, side reactions tend to proceed, and in some cases, there is a risk of air bubbles occurring in the epoxy resin cured product.

[0074] The component [c] in the epoxy resin composition for fiber-reinforced composite material of the present invention is a catalyst, which is a compound capable of promoting the curing reaction between the oxirane group contained in the component [a] and the isocyanate group contained in the component [b]. As the component [c] in such an epoxy resin composition, the same one as that explained in the molding method for the fiber-reinforced composite material of the present invention is preferably used.

[0075] The component [c] is preferably a salt of a Brønsted base and a Brønsted acid having a base dissociation constant pKb of 20 or more in acetonitrile. The component [c] is more preferably a salt of a Brønsted base and a Brønsted acid having a pKb of 24 or more, even more preferably a salt of a Brønsted base and a Brønsted acid having a pKb of 25 or more, and particularly preferably a salt of a Brønsted base and a Brønsted acid having a pKb of 26 or more. By including the component [c], excellent reactivity and reaction selectivity are exhibited. In the salt of a Brønsted base and a Brønsted acid, if the pKb of the Brønsted base is less than 20, the curing time may be extended, resulting in reduced productivity.

[0076] The base dissociation constant described here is the concentration of the base in the solvent, c (B), and the concentration of the conjugate acid of the base, c (BH + ), the concentration of protonated solvent c(SH + ) to obtain the equilibrium constant Kb = c(SH + )×c(B) / c(BH + ) and calculate the base dissociation constant pKb = -log 10 This value is calculated using Kb.

[0077] The base dissociation constant in acetonitrile can be calculated, for example, from a spectrum obtained by dissolving a base in acetonitrile, titrating with an acid, and measuring the spectrum in visible-ultraviolet spectroscopy.

[0078] Such a Bronsted base is not particularly limited as long as it is a base capable of accepting a proton in a neutralization reaction with an acid, but is preferably at least one type selected from the group consisting of amine compounds and imidazole compounds.

[0079] Examples of such Bronsted bases include amine compounds such as 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5-diazabicyclo[4.3.0]-5-nonene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 1,5,7-triazabicyclo[4.4.0]dec-5-ene; imidazole (melting point: 89° C.); 2-ethylimidazole (melting point: 80° C.); Examples of imidazole compounds include imidazole (melting point 72°C), 2-heptadecylimidazole (melting point 89°C), 1,2-dimethylimidazole (liquid at room temperature), 2-ethyl-4-methylimidazole (liquid at room temperature), 1-benzyl-2-phenylimidazole (liquid at room temperature), 1-benzyl-2-methylimidazole (liquid at room temperature), and 1-cyanoethyl-2-methylimidazole (liquid at room temperature).

[0080] The Brønsted acid in the salt of a Brønsted base having a base dissociation constant pKb of 20 or more in acetonitrile and a Brønsted acid is not particularly limited as long as it is an acid capable of donating a proton in a neutralization reaction with a base, but the acid dissociation constant pKa in water is preferably 5 or less, more preferably 3 or less, even more preferably 1.5 or less, and particularly preferably 0 or less. If it exceeds 5, the reaction that tends to increase the crosslink density tends to occur first, and the resulting cured product and fiber-reinforced composite material may become brittle. The Brønsted acid is preferably at least one selected from the group consisting of carboxylic acids, sulfonic acids, and hydrogen halides.

[0081] The acid dissociation constant explained here is the concentration of acid A in a dilute aqueous solution c(AH), the concentration of the conjugate base of acid A c(A - ), hydrogen ion concentration c(HO + ) to obtain the equilibrium constant Ka = c(HO + )×c(A - ) / c(AH) and calculate the acid dissociation constant pKa=-log 10 This value is calculated using Ka.

[0082] Such an acid dissociation constant can be calculated, for example, from the concentration of the substance in question and the hydrogen ion concentration measured using a pH meter.

[0083] Examples of such carboxylic acids include formic acid, acetic acid, oxalic acid, benzoic acid, phthalic acid, maleic acid, fumaric acid, malonic acid, tartaric acid, citric acid, lactic acid, succinic acid, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid, trifluoroacetic acid, nitroacetic acid, and triphenylacetic acid.

[0084] Examples of such sulfonic acids include methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid.

[0085] Examples of such hydrogen halides include hydrogen chloride, hydrogen bromide, and hydrogen iodide.

[0086] The component [c] preferably contains an onium salt whose anion is a halide, since this also exhibits excellent reactivity and reaction selectivity. As the onium salt, a quaternary ammonium salt or a quaternary phosphonium salt is preferably used.

[0087] Examples of such quaternary ammonium halides include trimethyloctadecyl ammonium chloride, trimethyloctadecyl ammonium bromide, benzyl trimethyl ammonium chloride, benzyl trimethyl ammonium bromide, tetrabutyl ammonium chloride, tetrabutyl ammonium bromide, (2-methoxyethoxymethyl) triethyl ammonium chloride, (2-methoxyethoxymethyl) triethyl ammonium bromide, (2-acetoxyethyl) trimethyl ammonium chloride, (2-acetoxyethyl) trimethyl ammonium bromide, (2-hydroxyethyl) trimethyl ammonium chloride, (2-hydroxyethyl) trimethyl ammonium bromide, bis(polyoxyethylene) dimethyl ammonium chloride, bis(polyoxyethylene) dimethyl ammonium bromide, 1-hexadecyl pyridinium chloride, and 1-hexadecyl pyridinium bromide.

[0088] Examples of such quaternary phosphonium halides include trimethyloctadecylphosphonium chloride, trimethyloctadecylphosphonium bromide, benzyltrimethylphosphonium chloride, benzyltrimethylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium bromide, (2-methoxyethoxymethyl)triethylphosphonium chloride, (2-methoxyethoxymethyl)triethylphosphonium bromide, (2-acetoxyethyl)trimethylphosphonium chloride, (2-acetoxyethyl)trimethylphosphonium bromide, (2-hydroxyethyl)trimethylphosphonium chloride, (2-hydroxyethyl)trimethylphosphonium bromide, bis(poly oxyethylene)dimethylphosphonium chloride, bis(polyoxyethylene)dimethylphosphonium bromide, tetraphenylphosphonium bromide, acetonyltriphenylphosphonium chloride, (4-carboxybutyl)triphenylphosphonium bromide, (4-carboxypropyl)triphenylphosphonium bromide, (2,4-dichlorobenzyl)triphenylphosphonium chloride, 2-dimethylaminoethyltriphenylphosphonium bromide, ethoxycarbonylmethyl(triphenyl)phosphonium bromide, (formylmethyl)triphenylphosphonium chloride, N-methylanilinotriphenylphosphonium iodide, phenacyltriphenylphosphonium bromide, and the like.

[0089] The total amount of the component [c] is preferably 1 part by mass or more and 10 parts by mass or less, more preferably 1 part by mass or more and 5 parts by mass or less, and even more preferably 1 part by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the total amount of the component [a]. If it is less than 1 part by mass, the curing time may be extended, which may lead to a decrease in productivity. On the other hand, if it exceeds 10 parts by mass, self-polymerization of the oxirane group contained in the component [a] may proceed, resulting in insufficient heat resistance.

[0090] In order to uniformly exert the catalytic action during the curing process, the component [c] is preferably a catalyst that can be dissolved in the epoxy resin of the component [a]. Here, the term "catalyst that can be dissolved in the epoxy resin of the component [a]" means that when 1 part by mass of the catalyst is added to the epoxy resin of the component [a] per 100 parts by mass of the total amount of the component [a], the mixture is heated to room temperature or to the vicinity of the melting point of the catalyst, kneaded at 200 rpm for 30 minutes, and left at room temperature for 1 hour, the two are uniformly compatible. As a means for confirming whether or not the two are uniformly compatible, a phase contrast microscope is used to judge whether or not there is any insoluble matter in the catalyst.

[0091] In addition to using each of the components [a] to [c] of the epoxy resin composition [B] described above, the first embodiment of the epoxy resin composition for fiber-reinforced composite materials of the present invention requires that when cured while increasing the temperature from 30° C. at a rate of 10° C. / min, a certain degree of cure X in which the absorbance ratio Da / (Da+Db) at the degree of cure X is in the range of 85 to 95% is in the range of 0.4 to 1. That is, in the first embodiment of the epoxy resin composition for fiber-reinforced composite materials of the present invention, when cured while increasing the temperature from 30° C. at a rate of 10° C. / min, the absorbance ratio Da / (Da+Db) at the degree of cure X in any range of 85 to 95% (for example, a degree of cure of 90%) is in the range of 0.4 to 1. The absorbance ratio Da / (Da+Db) described here is as described above. That is, it means a value calculated by using FT-IR by the ATR method, from the absorbance Da of the absorption due to the C=O double bond of the carboxyl group of the oxazolidone ring of the cured product of the epoxy resin composition, and the absorbance Db of the absorption due to the C=O double bond of the carboxyl group of the isocyanurate ring, as the absorbance ratio Da / (Da+Db). For example, when FT-IR (ATR method) is used with a resolution of 4 cm -1 When the measurement was performed 32 times, the result was 1760 cm -1 The absorbance of the absorption near 1710cm -1The degree of cure can be determined by calculating the degree of cure (%) = (QT-QR) / QT x 100 from the total heat release QT of the epoxy resin composition obtained by DSC at a heating rate of 10°C / min and the residual heat release QR of the cured product.

[0092] By setting the absorbance ratio Da / (Da+Db) at the specific degree of cure X to a range of 0.4 to 1, preferably 0.5 to 1, and more preferably 0.7 to 1, a structure with a low crosslink density can be formed while maintaining heat resistance, that is, leading to high toughness. If the absorbance ratio Da / (Da+Db) at the specific degree of cure X is lower than 0.4, the crosslink density becomes too high, and the strength and toughness of the cured product of the epoxy resin composition decrease. Note that the closer the absorbance ratio Da / (Da+Db) is to 1, the lower the crosslink density and the better the strength and toughness tend to be, which is a preferred embodiment.

[0093] In a first embodiment of the epoxy resin composition for fiber reinforced composite materials of the present invention, when the epoxy resin composition is cured while increasing the temperature from 30° C. at a rate of 10° C. / min, it is preferable that a certain degree of cure Y exists in a range of 15 to 25%, where the absorbance ratio Da / (Da+Db) at the degree of cure Y is in the range of 0.01 to 1. That is, in the first embodiment of the epoxy resin composition for fiber reinforced composite materials of the present invention, it is preferable that when the epoxy resin composition is cured while increasing the temperature from 30° C. at a rate of 10° C. / min, the absorbance ratio Da / (Da+Db) at a degree of cure of 15 to 25% (for example, a degree of cure of 20%) is in the range of 0.01 to 1.

[0094] By setting the absorbance ratio Da / (Da+Db) at the specific degree of cure Y in the range of 0.01 to 1, preferably in the range of 0.05 to 1, and more preferably in the range of 0.1 to 1, it is possible to suppress the reaction that occurs in advance and tends to increase the crosslink density, and it is also possible to avoid significant viscosity increase in the early stage of curing. If the absorbance ratio Da / (Da+Db) at the specific degree of cure Y is lower than 0.01, a highly heat-resistant structure can be expected, but the resulting fiber-reinforced composite material will be brittle. In addition, the viscosity will not be sufficient, leading to deterioration of surface quality.

[0095] In a second aspect of the epoxy resin composition for fiber-reinforced composite materials of the present invention, when an epoxy resin composition [B] similar to that in the first aspect is used and cured while increasing the temperature from 30°C at a rate of 10°C / min, it is essential that a certain degree of cure X, in which the relationship between the rubber state elastic modulus (Gr) and the glass transition temperature (Tg) at the degree of cure X satisfies Formula 1, is in the range of 85 to 95%.

[0096] During curing, oxazolidone rings are preferentially formed, resulting in the formation of a rigid molecular structure with low crosslink density, with the result that the relationship between Gr and Tg satisfies formula 1, preferably formula 1a, and more preferably formula 1b. As a result, a cured product and a fiber-reinforced composite material having high heat resistance and excellent toughness can be obtained. If the relationship between Gr and Tg does not satisfy formula 1, the balance between heat resistance and toughness of the obtained fiber-reinforced composite material will not be good. It is preferable that the relationship between Gr and Tg also satisfies formula 1'. Tg≧10×Gr+120 (Formula 1) Tg≧10×Gr+140 (Formula 1a) Tg≧10×Gr+160 (Formula 1b) Tg≦10×Gr+230 (Formula 1') In the second aspect of the epoxy resin composition for fiber reinforced composite materials of the present invention, when cured while increasing the temperature from 30°C at 10°C / min, it is preferable that a certain degree of cure X where the rubber state elastic modulus at the degree of cure X is in the range of 0.5 to 15 MPa is in the range of 85 to 95%, and it is more preferable that a certain degree of cure X where the rubber state elastic modulus at the degree of cure X is in the range of 0.5 to 10 MPa is in the range of 85 to 95%. That is, in the second aspect of the epoxy resin composition for fiber reinforced composite materials of the present invention, when cured while increasing the temperature from 30°C at 10°C / min, it is preferable that the rubber state elastic modulus at any of the ranges of 85 to 95% of cure (for example, 90% cure) is in the range of 0.5 to 15 MPa.

[0097] Since the rubber state elastic modulus at the specific degree of cure X is 0.5 to 15 MPa, the crosslink density can be appropriately controlled while introducing a rigid skeleton, and thus a matrix resin having both heat resistance and toughness can be obtained. If the rubber state elastic modulus at the specific degree of cure X is lower than 0.5 MPa, the crosslink density of the molecular chain is too low, and the obtained fiber reinforced composite material has poor heat resistance. If the rubber state elastic modulus at the specific degree of cure X is higher than 15 MPa, the crosslink density becomes too high, the resin elongation is not expressed, and the obtained fiber reinforced composite material has insufficient toughness.

[0098] The rubber state elastic modulus described here is a value measured as follows. That is, an epoxy resin composition is heat-cured into a plate having a thickness of about 2 mm, which is processed into a test piece having a width of 12±1 mm and a length of 30 to 40 mm, and then dynamic viscoelasticity is measured with a dynamic viscoelasticity measuring device at a temperature rise rate of 5°C / min. The rubber state elastic modulus is the storage elastic modulus at a temperature 50°C higher than the glass transition temperature obtained by dynamic viscoelasticity measurement. The glass transition temperature obtained by dynamic viscoelasticity measurement is the temperature at the intersection of a tangent drawn to the glass region and a tangent drawn to the glass transition region in the temperature-storage elastic modulus curve.

[0099] In a preferred embodiment of the epoxy resin composition for fiber-reinforced composite materials of the present invention, when the amount of hydroxyl groups is expressed in moles per 1 kg of the epoxy resin composition, the amount of hydroxyl groups in the epoxy resin composition is preferably 0.20 mol / kg or less, more preferably 0.17 mol / kg or less, even more preferably 0.13 mol / kg or less, even more preferably 0.09 mol / kg or less, even more preferably 0.06 mol / kg or less, and even more preferably 0.03 mol / kg or less. When the amount of hydroxyl groups in the epoxy resin composition exceeds 0.20 mol / kg, the reaction between the isocyanate group and the hydroxyl group in the composition proceeds to form a urethane bond, resulting in a significant decrease in heat resistance. In addition, such a reaction is likely to proceed at low temperatures, causing problems with storage stability during storage.

[0100] Here, the amount of hydroxyl groups in the epoxy resin composition is calculated by the following formula 3 using the hydroxyl equivalent for each of the constituent components. When the epoxy resin composition for fiber-reinforced composite materials of the present invention contains a component other than the constituent components [a] to [c] and the component contains a hydroxyl group (when a powder or granular component such as a filler or bulking agent has hydroxyl groups on its surface, the component contains a hydroxyl group), the component is also included in the above-mentioned components and used in the calculation by the following formula. COH=(Σ(wn / wnOH)) / W×1000 (Formula 3) COH: Amount of hydroxyl groups in the epoxy resin composition (mol / kg) wn: parts by mass of each component wnOH: Hydroxyl equivalent of each component (g / eq) W: Sum of mass parts of all components.

[0101] The hydroxyl equivalent of each component is the reciprocal of the hydroxyl value (the amount of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of the sample is acetylated, measured by the pyridine-acetyl chloride method in accordance with JIS K0070:1992, in mg KOH / g) divided by the formula weight of potassium hydroxide (56.11), and corresponds to the molecular weight per hydroxyl group (unit: g / eq). The "pyridine-acetyl chloride method" for measuring the hydroxyl equivalent of epoxy resins is specifically performed by dissolving the measured component in pyridine (dispersing the powdered component), adding an acetyl chloride-toluene solution, heating, cooling, and boiling to hydrolyze the excess acetyl chloride, and then titrating the resulting acetic acid with an ethanolic potassium hydroxide solution to measure the amount.

[0102] The epoxy resin composition for fiber-reinforced composite materials of the present invention, when cured while increasing the temperature from 30°C at 10°C / min, preferably has a specific degree of cure Z in the range of 5 to 15%, more preferably 0.05 or less, at which the ratio of urethane bonds to oxirane groups at the degree of cure Z is 0.10 or less. That is, the epoxy resin composition for fiber-reinforced composite materials of the present invention, when cured while increasing the temperature from 30°C at 10°C / min, preferably has a ratio of urethane bonds to oxirane groups at any of the range of 5 to 15% of the degree of cure (for example, a degree of cure of 10%) of 0.10 or less. If the ratio of urethane bonds to oxirane groups exceeds 0.10, the heat resistance and elastic modulus are insufficient, and the viscosity rise at low temperatures becomes significant, which may result in insufficient impregnation into reinforcing fibers.

[0103] The ratio of urethane bonds to oxirane groups described here is a value specified by calculating the area ratio of the number of protons of oxirane groups to the number of protons of urethane bonds in an epoxy resin composition obtained by nuclear magnetic resonance of the epoxy resin composition having the specific degree of cure Z. For example, using a high-resolution nuclear magnetic resonance analyzer (NMR measurement), 1Using H-NMR with 128 integrations, the proton adjacent to the carbon in the oxirane group of the epoxy resin at 2.7 ppm and the proton adjacent to the nitrogen in the urethane bond at 5.4 ppm can be observed with high resolution. 1 The area ratio of H-NMR reflects the number of moles, so the abundance ratio can be calculated.

[0104] The epoxy resin composition for fiber reinforced composite materials of the present invention preferably has a flexural modulus of 3.0 GPa or more and 6.0 GPa or less, and more preferably 3.4 GPa or more and 5.0 GPa or less, at a degree of cure of 85 to 95% (for example, a degree of cure of 90%). If the flexural modulus is less than 3.0 GPa, the compressive strength may be insufficient when the composition is made into a fiber reinforced composite material, and if it exceeds 6.0 GPa, the cutting surface may become rough when the composition is cut into a fiber reinforced composite material.

[0105] The epoxy resin composition for fiber reinforced composite materials of the present invention is preferably prepared by appropriately mixing the above-mentioned components so that the viscosity at 25°C is 0.1 to 1.0 Pa·s, more preferably 0.1 to 0.5 Pa·s. By making the viscosity at 25°C 1.0 Pa·s or less, the viscosity at the molding temperature can be lowered, the injection time into the reinforcing fiber substrate can be shortened, and the cause of non-impregnation can be prevented. In addition, by making the viscosity at 25°C 0.1 Pa·s or more, the viscosity at the molding temperature does not become too low, and pits caused by air entrapment during injection into the reinforcing fiber substrate can be prevented, and the occurrence of non-impregnated regions caused by uneven impregnation can be prevented. The viscosity at 25°C is measured immediately after the preparation of the epoxy resin composition.

[0106] The reinforcing fibers to be combined with the epoxy resin composition for fiber-reinforced composite materials of the present invention are not particularly limited, but the same methods as those used in the molding method for the fiber-reinforced composite material of the present invention are preferably used.

[0107] The form, configuration, etc. of the fiber-reinforced composite material to be combined with the epoxy resin composition for fiber-reinforced composite materials of the present invention are not particularly limited, but the same method as for molding the fiber-reinforced composite material of the present invention is preferably used. EXAMPLES

[0108] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0109] Examples 1 to 3, Reference Example 1, and Comparative Example 1 are as described below (including Table 1).

[0110] (1) Raw materials for epoxy resin composition The following raw materials were used to obtain the epoxy resin compositions of the examples. "jER (registered trademark)" 828 (bisphenol A type epoxy resin liquid, manufactured by Mitsubishi Chemical Corporation) "Lupranate (registered trademark)" M20S (Polymeric MDI, manufactured by BASF INOAC Polyurethanes Co., Ltd.) "DBU (registered trademark)" (1,8-diazabicyclo[5.4.0]undec-7-ene, manufactured by San-Apro Co., Ltd.) 3,3'-DAS (3,3'-diaminodiphenyl sulfone, manufactured by Mitsui Chemicals Fine Co., Ltd.).

[0111] (2) Preparation of epoxy resin composition In Examples 1 to 3 and Reference Example 1, 100 parts by mass of "jER (registered trademark)" 828 and 4 parts by mass of "DBU (registered trademark)" were added as epoxy resins and kneaded to obtain a transparent viscous liquid. Then, 72 parts by mass of "Lupranate (registered trademark)" M20S was added and further kneaded to obtain an epoxy resin composition.

[0112] In Comparative Example 1, 75 parts by mass of "jER (registered trademark)" 828 and 25 parts by mass of 3,3'-DAS were added as the epoxy resin, and further kneaded to obtain an epoxy resin composition.

[0113] (3) Preparation of epoxy resin cured plate The epoxy resin cured product prepared in (2) above was degassed in a vacuum and then poured into a preheated plate. A cured epoxy resin plate was produced using a dynamic viscoelasticity tester (ATD: manufactured by Alpha Technologies LLC) under the curing conditions shown in Table 1.

[0114] (4) Measurement of the degree of curing of epoxy resin cured boards 5 mg of the epoxy resin composition prepared in (2) above was sampled and measured using a differential scanning calorimeter (DSC2910: manufactured by TA Instruments) by increasing the temperature from 30°C to 350°C at a heating rate of 10°C / min to obtain an exothermic curve, and the total heat generation amount QT of the thermosetting resin was calculated by integrating the exothermic peak. When exothermic or endothermic peaks due to decomposition reactions or the like were observed, the measurement was performed in the temperature range below those peaks.

[0115] 10 mg of the epoxy resin cured plate prepared in (3) above or taken out after a certain time has elapsed since the start of curing was sampled, and the temperature was increased from 30°C to 350°C at a rate of 10°C / min using a differential scanning calorimeter (DSC2910: manufactured by TA Instruments), and the heat generation curve was obtained. The heat generation peak was integrated to calculate the residual heat generation amount QR of the cured epoxy resin. When heat generation or endothermic peaks due to decomposition reactions or the like were observed, the measurement was performed in the temperature range below those peaks.

[0116] Here, the degree of cure (%) obtained by DSC was calculated by the formula: degree of cure (%)=(QT-QR) / QT×100.

[0117] Furthermore, from this measurement, the time required for the epoxy resin composition to reach a certain degree of cure within a range of 15 to 25% (in this example, a degree of cure of 20%) was calculated.

[0118] (5) Measurement of glass transition temperature of cured epoxy resin sheet A 10 mg sample was taken from the epoxy resin cured plate prepared in (3) above, and the temperature was measured from 30°C to 350°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC2910: manufactured by TA Instruments). The midpoint temperature calculated based on JIS K7121:1987 was taken as the glass transition temperature Tg, and the heat resistance was evaluated.

[0119] (6) Measurement of bending deflection of epoxy resin cured plate The surface of the epoxy resin cured plate prepared in (3) above was polished with sandpaper of #240, #800, and #2000 to obtain an epoxy resin cured plate of 2 mm in thickness. Next, a test piece of 10 mm in width and 60 mm in length was cut out from the obtained epoxy resin cured plate, and a three-point bending test with a span of 32 mm was performed to determine the bending deflection amount, which is an index of resin toughness, according to JIS K7171:1994.

[0120] (7) Measurement of absorbance ratio of epoxy resin cured board The epoxy resin cured plate prepared in (3) above or an epoxy resin cured plate having a specific degree of cure within the range of 15 to 25% (in this embodiment, the degree of cure is 20%) was sampled, and FT-IR (ATR method) was performed using an FT-IR device (7000FT-IR: manufactured by Varian). The measurement conditions were a resolution of 4 cm -1 The number of integration times was set to 32.

[0121] The absorbance ratio Da / (Da+Db) is the 1760 cm -1 The absorbance Da of the absorption near 1710 cm due to the C=O double bond of the carboxyl group of the isocyanurate ring -1 It was calculated from the absorbance Db of the nearby absorption.

[0122] (8) Mass loss measurement of epoxy resin cured plate by TGA 10 mg of the epoxy resin cured plate prepared in (3) above was sampled, and the mass loss rate was measured using a thermogravimetric analyzer (TGA7: manufactured by PerkinElmer) under conditions of nitrogen (purity: 99.99% or more) flow, program temperature of 50°C was held for 1 minute, and the temperature was increased from 50°C to 800°C at a heating rate of 20°C / min.

[0123] The mass reduction rate ΔWr was calculated from the sample mass W1 when the temperature reached 70°C and the sample mass W2 when the temperature reached 320°C during the temperature rise process as follows: mass reduction rate ΔWr (%) = (W1-W2) / W1×100.

[0124] (9) Fabrication of fiber-reinforced composite materials A mold with a plate-shaped cavity of 350 mm x 700 mm x 2 mm was filled with carbon fiber fabric CO6343 (carbon fiber: T300-3K, structure: plain weave, weight: 198 g / m) as reinforcing fiber. 2 Nine sheets of epoxy resin (manufactured by Toray Industries, Inc.) were stacked in the cavity, and the mold was clamped with a press. Next, the pressure inside the mold, which was kept at 100°C (molding temperature), was reduced to atmospheric pressure -0.1 MPa using a vacuum pump, and epoxy resin compositions that had been preheated to 50°C were mixed using a resin injector and injected at a pressure of 0.2 MPa. The mixture was then cured under the curing conditions shown in Table 1, and demolded to obtain a fiber-reinforced composite material.

[0125] (10) Measurement of glass transition temperature of fiber-reinforced composite materials A 10 mg sample was taken from the fiber-reinforced composite material prepared in (9) above, and the temperature was measured by raising the temperature from 30°C to 350°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC2910: manufactured by TA Instruments). The midpoint temperature calculated based on JIS K7121:1987 was taken as the glass transition temperature Tg, and the heat resistance was evaluated.

[0126] Example 1 As described above, cured products of epoxy resin compositions and fiber-reinforced composite materials were prepared under the curing conditions shown in Table 1. The cured products of such epoxy resin compositions had no problem with heat resistance and ΔWr, and had excellent toughness.

[0127] Example 2 The curing conditions were changed from those in Example 1. The cured product of this epoxy resin composition had an acceptable level of heat resistance and was excellent in toughness and ΔWr.

[0128] Example 3 The curing conditions were changed from those in Example 1. The cured product of this epoxy resin composition had excellent heat resistance, toughness and ΔWr.

[0129] (Reference example 1) The curing conditions were changed from those in Example 1. The cured product of this epoxy resin composition had poor Da / (Da+Db) and excellent heat resistance, but was poor in toughness and ΔWr.

[0130] Comparative Example 1 An amine compound was added as a curing agent other than the component [b]. The cured product of such an epoxy resin composition did not form an oxazolidone ring, and was inferior in heat resistance and ΔWr.

[0131] [Table 1]

[0132] Examples 4 to 27 and Comparative Examples 2 to 8 are as described below (including Tables 2-1 to 2-4).

[0133] (1) Raw materials for epoxy resin composition The following raw materials were used to obtain the epoxy resin compositions of the examples. [a] Epoxy resin having at least two oxirane groups in the molecule "jER (registered trademark)" 828 (bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation) "Epototo (registered trademark)" YD-8125 (bisphenol A type epoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.) "EPICLON (registered trademark)" 830 (bisphenol F type epoxy resin, manufactured by DIC Corporation) Modified YD-8125 10 parts by mass of acetic anhydride was added to 100 parts by mass of "Epotohto (registered trademark)" YD-8125, and the mixture was heated and stirred at 110°C for 1 hour to acetylate the small amount of hydroxyl groups contained in YD-8125. The mixture was then heated in a vacuum at 110°C to remove excess acetic acid and the acetic acid produced, yielding a modified YD-8125 product. "Denacol" EX-313 (glycerin type epoxy resin, 1,3-bis(oxiranylmethoxy)propan-2-ol, manufactured by Nagase ChemteX Corporation) "Araldite (registered trademark)" MY0510 (triglycidyl-p-aminophenol, manufactured by Huntsman Advanced Materials) "Araldite(R)" MY721 (tetraglycidyldiaminodiphenylmethane, manufactured by Huntsman Advanced Materials).

[0134] [b] An epoxy resin curing agent having at least two isocyanate groups "Lupranate (registered trademark)" M20S (Polymeric MDI, manufactured by BASF INOAC Polyurethanes Co., Ltd.) "Lupranate (registered trademark)" MI (monomeric MDI, manufactured by BASF INOAC Polyurethanes Ltd.).

[0135] [c]Catalyst "DBU (registered trademark)" (1,8-diazabicyclo[5.4.0]undec-7-ene, manufactured by San-Apro Co., Ltd., pKb=25) "DBU" / phthalic acid (Tokyo Chemical Industry Co., Ltd., pKa=3) salt "DBU" / dichloroacetic acid (Tokyo Chemical Industry Co., Ltd., pKa=1.5) salt "DBU" / p-toluenesulfonic acid (Tokyo Chemical Industry Co., Ltd., pKa=-3) salt "DBN (registered trademark)" (1,5-diazabicyclo[4.3.0]-5-nonene, manufactured by San-Apro Co., Ltd., pKb=24) / phthalate TBD (1,5,7-triazabicyclo[4.4.0]dec-5-ene, Tokyo Chemical Industry Co., Ltd., pKb=26) / dichloroacetate · TBAB (Tetrabutylammonium bromide, manufactured by Tokyo Chemical Industry Co., Ltd.) "Hokuko TBP-BB (registered trademark)" (tetrabutylphosphonium bromide, manufactured by Hokko Chemical Industry Co., Ltd.).

[0136] Epoxy resin other than [a] BGE (4-tert-butylphenyl glycidyl ether, manufactured by Tokyo Chemical Industry Co., Ltd.).

[0137] [b] Epoxy resin curing agent having an isocyanate group other than 2-Phenylethyl isocyanate (Tokyo Chemical Industry Co., Ltd.).

[0138] Components other than [a]-[c] -Polypropylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). -“LonzaCure(R)” M-DEA (manufactured by Huntsman Advanced Materials).

[0139] (2) Preparation of epoxy resin composition The epoxy resin and catalyst were mixed in the mixing ratio (mass ratio) shown in Tables 2-1 to 2-4, and after confirming dissolution with a phase contrast microscope, an epoxy resin curing agent was added to prepare an epoxy resin composition.

[0140] (3) Hydroxyl group content of epoxy resin composition The amount of hydroxyl groups in the epoxy resin composition was calculated using the hydroxyl equivalent of each component of the constituent elements according to Equation 3. COH=(Σ(wn / wnOH)) / W×1000 (Formula 3) COH: Amount of hydroxyl groups in the epoxy resin composition (mol / kg) wn: parts by mass of each component wnOH: Hydroxyl equivalent of each component (g / eq) W: Sum of mass parts of all components.

[0141] The hydroxyl equivalent of each component was determined by titrating the hydroxyl value (unit: mgKOH / g) of the component [a] using the pyridine-acetyl chloride method in accordance with JIS K0070:1992, and dividing this by the formula weight of potassium hydroxide (56.11) to calculate the amount of hydroxyl groups (unit: mmol / g). The "pyridine-acetyl chloride method" for measuring the hydroxyl equivalent of an epoxy resin is specifically performed by dissolving the resin to be measured in pyridine, adding an acetyl chloride-toluene solution, heating, cooling, and then boiling to hydrolyze the excess acetyl chloride, and then titrating the resulting acetic acid with an ethanolic potassium hydroxide solution.

[0142] (4) Viscosity measurement of epoxy resin composition Using a dynamic viscoelasticity measuring device (ARES: manufactured by TA Instruments), a parallel plate with a diameter of 40 mm was used, and the complex viscosity η obtained under the measurement conditions of a simple temperature rise rate of 1.5°C / min, a frequency of 1 Hz, and a gap of 1 mm was measured. * The value at 25°C was used.

[0143] (5) Preparation of epoxy resin cured plate The epoxy resin composition prepared in (2) above was degassed in a vacuum and then poured into a preheated plate. Using a dynamic viscoelasticity tester (ATD: manufactured by Alpha Technologies LLC), the temperature was raised at a rate of 10°C / min from 30°C to a temperature at which the degree of cure obtained in the measurement described in (6) was 90%, thereby producing a cured epoxy resin plate.

[0144] (6) Measurement of the degree of curing of epoxy resin cured sheets 5 mg of the epoxy resin composition prepared in (2) above was sampled and measured using a differential scanning calorimeter (DSC2910: manufactured by TA Instruments) by increasing the temperature from 30°C to 350°C at a heating rate of 10°C / min to obtain an exothermic curve, and the total heat generation amount QT of the thermosetting resin was calculated by integrating the exothermic peak. When exothermic or endothermic peaks due to decomposition reactions or the like were observed, the measurement was performed in the temperature range below those peaks.

[0145] 10 mg of the epoxy resin cured plate prepared in (5) above was sampled and measured using a differential scanning calorimeter (DSC2910: manufactured by TA Instruments) by increasing the temperature from 30°C to 350°C at a heating rate of 10°C / min to obtain a heat generation curve, and the residual heat generation amount QR of the cured epoxy resin was calculated by integrating the heat generation peak. When heat generation or endothermic peaks due to decomposition reactions or the like were observed, the measurement was performed in the temperature range below those peaks.

[0146] Here, the degree of cure (%) obtained by DSC was calculated by the formula: degree of cure (%)=(QT-QR) / QT×100.

[0147] Furthermore, from this measurement, the temperatures at which the epoxy resin composition reaches a specific degree of cure X (in this embodiment, a degree of cure of 90%), a specific degree of cure Y (in this embodiment, a degree of cure of 20%), and a specific degree of cure Z (in this embodiment, a degree of cure of 10%) were calculated.

[0148] (7) Ratio of urethane bonds and oxirane groups at a specific degree of cure Z The epoxy resin cured product with a specific degree of cure Z (10% in this example) prepared in (5) above was sampled and measured in deuterated chloroform solvent using 500 MHz 1H-NMR with 128 cumulative measurements. The abundance ratio was calculated from the area value of the proton adjacent to the carbon in the oxirane group of the epoxy resin at 2.7 ppm and the proton adjacent to the nitrogen in the urethane bond at 5.4 ppm.

[0149] (8) Absorbance ratio measurement at specific cure degrees X and Y The epoxy resin cured products with a specific degree of cure X (90% in this example) and a specific degree of cure Y (20% in this example) prepared in (5) above were sampled and subjected to FT-IR (ATR method) using an FT-IR device (7000FT-IR: manufactured by Varian). The measurement conditions were a resolution of 4 cm -1 The number of integration times was set to 32.

[0150] The absorbance ratio Da / (Da+Db) is the 1760 cm -1 The absorbance Da of the absorption near 1710 cm due to the C=O double bond of the carboxyl group of the isocyanurate ring -1 It was calculated from the absorbance Db of the nearby absorption.

[0151] (9) Measurement of glass transition temperature at a specific degree of cure X 10 mg of a sample was taken from the cured epoxy resin having a degree of cure of X (90% in this embodiment) prepared in (5) above, and the sample was measured by heating from 30°C to 350°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC2910: manufactured by TA Instruments). The midpoint temperature calculated in accordance with JIS K7121:1987 was taken as the glass transition temperature Tg, and the heat resistance was evaluated.

[0152] (10) Rubber-state elastic modulus measurement at a specific cure degree X A test piece with a width of 10 mm and a length of 40 mm was cut out from the epoxy resin cured product with a degree of cure of X (90% in this embodiment) prepared in (5) above, and a dynamic viscoelasticity measuring device (ARES: manufactured by TA Instruments) was used to set the test piece on a solid twisting jig, and measurements were performed in the temperature range of 30 to 300°C at a heating rate of 5°C / min, a frequency of 1Hz, and a strain of 0.1%. The rubber-state elastic modulus, which is an index of crosslink density, was the storage elastic modulus at a temperature 50°C higher than the glass transition temperature obtained by dynamic viscoelasticity measurement. The glass transition temperature obtained by dynamic viscoelasticity measurement was the temperature at the intersection of a tangent drawn to the glass region and a tangent drawn to the glass transition region in the temperature-storage elastic modulus curve.

[0153] (11) Measurement of bending modulus and bending deflection at a specific degree of hardening X The surface of the cured epoxy resin product having a degree of cure of X (90% in this embodiment) prepared in (5) above was polished with sandpapers of #240, #800, and #2000 to obtain a cured epoxy resin plate of 2 mm in thickness. From the cured epoxy resin plate obtained, a test piece of 10 mm in width and 60 mm in length was cut out and subjected to a three-point bending test with a span of 32 mm to determine the bending modulus and bending deflection, which is an index of resin toughness, in accordance with JIS K7171:1994.

[0154] Example 4 As described above, epoxy resin compositions were prepared in the content ratios shown in Table 2-1. The epoxy resin compositions had excellent viscosity at 25° C. The epoxy resin compositions had excellent heat resistance, toughness, and elastic modulus at a degree of cure of 90%.

[0155] Example 5 In Example 4, the component [a] was changed to an epoxy resin having a small amount of hydroxyl groups. This epoxy resin composition had particularly excellent viscosity at 25°C. The epoxy resin composition had excellent heat resistance and elastic modulus at a degree of cure of 90%, and was particularly excellent in toughness.

[0156] Example 6 The component [a] in Example 4 was changed to a bisphenol F type epoxy resin. This epoxy resin composition had a particularly excellent viscosity at 25°C. The epoxy resin composition had no problem with heat resistance at a degree of cure of 90%, and had excellent toughness and elastic modulus.

[0157] (Examples 7 to 11) The component [c] in Example 4 was changed to a salt of a Brønsted base and a Brønsted acid. The epoxy resin composition had excellent viscosity at 25°C. The epoxy resin composition had no problem with heat resistance at a degree of cure of 90%, and had excellent toughness and elastic modulus.

[0158] (Examples 12 and 13) The component [c] in Example 4 was changed to an onium halide salt. The epoxy resin composition had excellent viscosity at 25°C. The epoxy resin composition had no problem with heat resistance at a degree of cure of 90%, and had excellent toughness and elastic modulus.

[0159] Example 14 The amount of the component [c] was changed to 1 part by mass from Example 4. The epoxy resin composition had an excellent viscosity at 25° C. The heat resistance and elastic modulus of the epoxy resin composition at a degree of cure of 90% were at acceptable levels, and the toughness was excellent.

[0160] Example 15 The amount of the component [c] was changed to 10 parts by mass from Example 4. The epoxy resin composition had an acceptable viscosity at 25°C. The epoxy resin composition had excellent heat resistance and elastic modulus at a degree of cure of 90%, and had an acceptable toughness.

[0161] Example 16 The ratio of the number of isocyanate groups in the component [b] to the number of oxirane groups in the epoxy resin composition was changed to 0.8 from Example 4. This epoxy resin composition had excellent viscosity at 25°C. The heat resistance and elastic modulus of the epoxy resin composition at a degree of cure of 90% were at acceptable levels, and the toughness was excellent.

[0162] (Example 17) In Example 4, the ratio of the number of isocyanate groups in the component [b] to the number of oxirane groups in the epoxy resin composition was changed to 0.5. The viscosity of this epoxy resin composition at 25°C was at an acceptable level. Although the heat resistance and elastic modulus of the epoxy resin composition at a degree of cure of 90% were poor, the toughness was at an acceptable level.

[0163] (Example 18) From Example 4, the ratio of the number of isocyanate groups in the component [b] to the number of oxirane groups in the epoxy resin composition was changed to 1.1. Such an epoxy resin composition had an excellent viscosity at 25°C. The epoxy resin composition had excellent heat resistance and elastic modulus at a degree of cure of 90%, and the toughness was at an acceptable level.

[0164] (Example 19) In Example 4, the ratio of the number of isocyanate groups in the component [b] to the number of oxirane groups in the epoxy resin composition was changed to 1.4. Such an epoxy resin composition had an excellent viscosity at 25°C. The epoxy resin composition had excellent heat resistance and elastic modulus at a degree of cure of 90%, and the toughness was at an acceptable level.

[0165] (Example 20) The ratio of the number of isocyanate groups in the component [b] to the number of oxirane groups in the epoxy resin composition was changed to 1.7 from Example 4. Such an epoxy resin composition had an excellent viscosity at 25°C. The epoxy resin composition had excellent heat resistance and elastic modulus at a degree of cure of 90%, and the toughness was at an acceptable level.

[0166] Example 21 The type of component [b] was changed from that in Example 4. This epoxy resin composition had an excellent viscosity at 25°C. The heat resistance and elastic modulus of the epoxy resin composition at a degree of cure of 90% were at acceptable levels, and the toughness was excellent.

[0167] Example 22 Thirty percent of the component [a] was changed to an epoxy resin with a low hydroxyl group content from Example 4. This epoxy resin composition had a slightly superior viscosity at 25°C, and the heat resistance and toughness of the epoxy resin composition at a degree of cure of 90% were also improved.

[0168] Example 23 The amount of the epoxy resin having a low hydroxyl group content, component [a], was increased to 70% in comparison with Example 22. The viscosity of this epoxy resin composition at 25°C was further improved, and the heat resistance and toughness of the epoxy resin composition at a degree of cure of 90% were also further improved.

[0169] (Example 24) The component [a] in Example 4 was changed to a tetrafunctional amine-type epoxy resin. This epoxy resin composition had particularly excellent viscosity at 25°C. The epoxy resin composition had particularly excellent heat resistance and elastic modulus at a degree of cure of 90%, and had an acceptable level of toughness.

[0170] (Example 25) The component [a] in Example 4 was changed to a combination of bisphenol F type epoxy and trifunctional amine type epoxy resin. This epoxy resin composition had excellent viscosity at 25°C. The epoxy resin composition had particularly excellent heat resistance and elastic modulus at a degree of cure of 90%, and also had excellent toughness.

[0171] (Example 26) The component [a] in Example 4 was changed to a combination of bisphenol F type epoxy and tetrafunctional amine type epoxy resin. This epoxy resin composition had excellent viscosity at 25°C. The epoxy resin composition had particularly excellent heat resistance and elastic modulus at a degree of cure of 90%, and also had excellent toughness.

[0172] Example 27 In Example 5, the component [a] was changed to an epoxy resin with a smaller amount of hydroxyl groups. This epoxy resin composition had a more excellent viscosity at 25°C, and the heat resistance and toughness of the epoxy resin composition at a degree of cure of 90% were also further improved.

[0173] Comparative Example 2 A glycerin-type epoxy resin was blended as component [a], but it had poor viscosity at 25°C, heat resistance at a degree of cure of 90%, and elastic modulus.

[0174] Comparative Example 3 A monofunctional epoxy resin was blended as component [a], but it had poor viscosity at 25°C, heat resistance at a degree of cure of 90%, toughness, and elastic modulus.

[0175] Comparative Example 4 A monofunctional isocyanate was blended as component [b], and the viscosity at 25°C, heat resistance at a degree of cure of 90%, toughness, and elastic modulus were poor.

[0176] Comparative Example 5 By not including component [c], a hardened material with a degree of cure of 90% could not be obtained under the specified conditions.

[0177] Comparative Example 6 This is similar to Example I12 in Patent Document 1 (WO 2014 / 184082). Many isocyanurate rings were formed, and the toughness was poor.

[0178] Comparative Example 7 This is similar to Example 1 of Patent Document 2 (WO 2016 / 102358). By blending a polyol into the resin composition, the amount of hydroxyl groups was significantly increased, and many urethane bonds were formed, resulting in poor viscosity at 25°C, heat resistance at a degree of cure of 90%, and elastic modulus.

[0179] Comparative Example 8 When component [c] was not included and an amine curing agent was used instead of component [b], the viscosity at 25°C, heat resistance at a degree of cure of 90%, and elastic modulus were inferior.

[0180] [Table 2-1]

[0181] [Table 2-2]

[0182] [Table 2-3]

[0183] [Table 2-4] [Industrial Applicability]

[0184] The present invention provides an epoxy resin composition for fiber-reinforced composite materials, which has a low viscosity when injected into reinforcing fibers, excellent impregnation properties, high toughness and high heat resistance, and a high elastic modulus, and a fiber-reinforced composite material using the same, because the resin composition has a viscosity stability at low temperatures. This is expected to promote the application of fiber-reinforced composite materials, particularly in aircraft and automobile applications, and contribute to improving fuel efficiency through further weight reduction and reducing greenhouse gas emissions.

Claims

1. A method for molding a fiber-reinforced composite material comprising at least reinforcing fibers [A] and a cured product of an epoxy resin composition [B], wherein the epoxy resin composition [B] contains the following components [a], [b], and [c] and has a hydroxyl group amount of 0.09 mol / kg or less, and the epoxy resin composition [B] is cured so that an absorbance ratio Da / (Da+Db) is in the range of 0.4 to 1 to obtain the fiber-reinforced composite material. [a] An epoxy resin having at least two oxirane groups in the molecule [b] An epoxy resin curing agent having at least two isocyanate groups in the molecule [c] Catalyst (Here, the absorbance ratio is determined by calculating the absorbance ratio Da / (Da+Db) from the absorbance Da of the absorption due to the C=O double bond of the carboxyl group of the oxazolidone ring and the absorbance Db of the absorption due to the C=O double bond of the carboxyl group of the isocyanurate ring in FT-IR (ATR method).)

2. The method for molding a fiber-reinforced composite material according to claim 1, wherein the epoxy resin composition [B] is cured so that the absorbance ratio Da / (Da+Db) at a specific degree of cure within a range of 15 to 25% is in the range of 0.01 to 1. (The degree of cure is determined by calculating the degree of cure (%) = (QT - QR) / QT x 100 from the total heat release amount QT of the epoxy resin composition obtained by DSC at a heating rate of 10°C / min and the residual heat release amount QR of the cured product.)

3. 3. The method for molding a fiber-reinforced composite material according to claim 1 or 2, wherein the epoxy resin composition [B] is cured so that the absorbance ratio is in the range of 0.7 to 1 to obtain a fiber-reinforced composite material.

4. A method for molding a fiber-reinforced composite material comprising at least reinforcing fibers [A] and a cured product of an epoxy resin composition [B], wherein the epoxy resin composition [B] contains the following components [a], [b], and [c] and has a hydroxyl group amount of 0.09 mol / kg or less, and the epoxy resin composition [B] is cured so that the relationship between a rubber-state elastic modulus (Gr) and a glass transition temperature (Tg) satisfies Formula 1 to obtain a fiber-reinforced composite material. [a] An epoxy resin having at least two oxirane groups in the molecule [b] An epoxy resin curing agent having at least two isocyanate groups in the molecule [c] Catalyst Tg≧10×Gr+120 (Formula 1)

5. The method for molding a fiber-reinforced composite material according to claim 4, further comprising curing the epoxy resin composition [B] so as to satisfy formula 2 to obtain a fiber-reinforced composite material. 0.5≦Gr≦15 (Formula 2)

6. The method for molding a fiber-reinforced composite material according to any one of claims 1 to 5, wherein a cured product of the epoxy resin composition [B] constituting the fiber-reinforced composite material has a mass reduction rate ΔWr in the range of 10% or less. (Here, the mass reduction rate is determined by calculating the mass reduction rate ΔWr(%)=(W1-W2) / W1×100 from the mass W1 at the time when the temperature reaches 70° C. and the mass W2 of the sample at the time when the temperature reaches 320° C. when thermogravimetric analysis is performed at a temperature rise rate of 10° C. / min from 50° C. to 800° C. in a non-oxidizing atmosphere at normal pressure.)

7. The method for molding a fiber-reinforced composite material according to any one of claims 1 to 6, wherein the epoxy resin composition [B] is injected into a substrate made of the reinforcing fiber [A] placed in a molding die heated to 100 to 200°C, impregnated with the epoxy resin composition [B], and cured in the molding die.

8. The method for molding a fiber-reinforced composite material according to any one of claims 1 to 7, wherein the epoxy resin composition [B] heated to 30 to 80°C is injected into a substrate made of the reinforcing fiber [A] placed in a molding die heated to 120 to 180°C, impregnated therein, and cured in the molding die.

9. 9. The method for molding a fiber-reinforced composite material according to claim 7 or 8, wherein when the epoxy resin composition [B] is injected into the substrate made of the reinforcing fiber [A] placed in a molding die, the resin is injected from a plurality of positions provided in the molding die.

10. An epoxy resin composition for use in a fiber-reinforced composite material, comprising the following components [a], [b], and [c], having a hydroxyl group amount of 0.09 mol / kg or less, and when cured while increasing the temperature from 30°C at a rate of 10°C / min, the absorbance ratio Da / (Da+Db) at the degree of cure X is in the range of 0.4 to 1, and the degree of cure X is in the range of 85 to 95%. [a] An epoxy resin having at least two oxirane groups in the molecule [b] An epoxy resin curing agent having at least two isocyanate groups in the molecule [c] Catalyst (Here, the absorbance ratio is determined by calculating the absorbance ratio Da / (Da+Db) from the absorbance Da of the absorption due to the C=O double bond of the carboxyl group of the oxazolidone ring and the absorbance Db of the absorption due to the C=O double bond of the carboxyl group of the isocyanurate ring in FT-IR (ATR method). The degree of cure is determined by calculating the degree of cure (%)=(QT-QR) / QT×100 from the total heat generation amount QT of the epoxy resin composition obtained by DSC at a heating rate of 10° C. / min and the residual heat generation amount QR of the cured product.)

11. 11. The epoxy resin composition for fiber-reinforced composite materials according to claim 10, wherein, when cured while increasing the temperature from 30°C at a rate of 10°C / min, a specific degree of cure Y at which the absorbance ratio Da / (Da+Db) at the degree of cure Y is in the range of 0.01 to 1 is in the range of 15 to 25%.

12. An epoxy resin composition for use in a fiber-reinforced composite material, comprising the following components [a], [b], and [c], having a hydroxyl group amount of 0.09 mol / kg or less, and when cured while increasing the temperature from 30°C at a rate of 10°C / min, a specific degree of cure X exists in the range of 85 to 95%, where the relationship between the rubber-state elastic modulus (Gr) and the glass transition temperature (Tg) at the degree of cure X satisfies Equation 1: [a] An epoxy resin having at least two oxirane groups in the molecule [b] An epoxy resin curing agent having at least two isocyanate groups in the molecule [c] Catalyst Tg≧10×Gr+120 (Formula 1)

13. 13. The epoxy resin composition for fiber reinforced composite materials according to claim 12, wherein when cured while increasing the temperature from 30°C at a rate of 10°C / min, a certain degree of cure X in which the rubber state elastic modulus at the degree of cure X is in the range of 0.5 to 15 MPa is in the range of 85 to 95%.

14. The epoxy resin composition for fiber-reinforced composite materials according to any one of claims 10 to 13, comprising one or more amine-type epoxy resins as component [a].

15. The epoxy resin composition for fiber-reinforced composite materials according to any one of claims 10 to 14, comprising one or more bisphenol-type epoxy resins as component [a].

16. 16. The epoxy resin composition for fiber-reinforced composite materials according to any one of claims 10 to 15, wherein a ratio of the number of moles of isocyanate groups of the component [b] to the number of moles of oxirane groups of all epoxy resins contained in the epoxy resin composition is 0.5 to 1.

8.

17. 17. The epoxy resin composition for a fiber-reinforced composite material according to any one of claims 10 to 16, comprising, as the component [c], a salt of a Brønsted base having a base dissociation constant pKb in acetonitrile of 20 or more and a Brønsted acid.

18. 18. The epoxy resin composition for a fiber-reinforced composite material according to claim 17, wherein the Bronsted acid has an acid dissociation constant pKa in water of 5 or less.

19. 19. The epoxy resin composition for a fiber-reinforced composite material according to claim 17 or 18, wherein the Bronsted base is at least one selected from the group consisting of an amine compound and an imidazole compound.

20. The epoxy resin composition for fiber-reinforced composite materials according to any one of claims 17 to 19, wherein the Bronsted acid is at least one selected from the group consisting of carboxylic acids, sulfonic acids and hydrogen halides.

21. The epoxy resin composition for a fiber-reinforced composite material according to any one of claims 10 to 16, comprising, as the component [c], an onium salt whose anion is a halide ion.

22. 22. The epoxy resin composition for fiber-reinforced composite materials according to claim 21, wherein the onium salt is at least one selected from the group consisting of quaternary ammonium salts and quaternary phosphonium salts.

23. 23. The epoxy resin composition for fiber-reinforced composite materials according to any one of claims 10 to 22, wherein the component [c] is 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the total amount of the component [a].

24. The epoxy resin composition for fiber-reinforced composite materials according to any one of claims 10 to 23, wherein the component [c] is soluble in the component [a].

25. 25. The epoxy resin composition for fiber-reinforced composite materials according to any one of claims 10 to 24, wherein, when cured while increasing the temperature from 30°C at a rate of 10°C / min, a specific degree of cure Z at which the abundance ratio of urethane bonds and oxirane groups at the degree of cure Z is 0.10 or less is in the range of 5 to 15%.

26. The epoxy resin composition for fiber reinforced composite materials according to any one of claims 10 to 25, having a viscosity at 25°C of 0.1 to 1.0 Pa·s.

27. A cured product of the epoxy resin composition for fiber reinforced composite materials according to any one of claims 10 to 26.

28. A fiber-reinforced composite material comprising the cured product according to claim 27 and reinforcing fibers.

Citation Information

Patent Citations

  • Manufacture of forming substance

    JP1985020922A

  • Manufacture of reactive resin forming substance

    JP1985069121A

  • The epoxy-terminated Polyoxazolidone, preparation, and is made from a laminated sheet

    JP1992506678A

  • Oxazolidinone and isocyanurate crosslinked matrices for fiber reinforced materials

    JP2018501391A

  • Cured compositions based on epoxy resins and polyisocyanates having high impact strength and high temperature resistance

    JP2019521216A